Industry relevant microfluidic platforms for mineral leaching experiments - Yang, Daisy; Priest, Craig (Frontiers in Chemical Engineering, 2024)
Microfluidic and lab-on-a-chip devices offer exquisite temporal and spatial control over chemical and physical processes that are important in mineral exploration and mining. These include mineral-water interfacial reactions, dissolution, and adsorption/desorption in pores, fractures, or other micro/nanostructures. Microfluidic mineral studies offer advantages of small sample and reagent volumes, high throughout, and short analytical cycles that may enable in-field mining decisions. However, not many microfluidic studies have targeted these mining sector challenges for mineral leaching. In this review, special attention is given to microscale experimental platforms for predicting extraction and leaching of industrially-relevant samples (real ore samples). Advantages and challenges of these platforms are given. The review concludes that there are significant opportunities for microfluidics in mineral analysis, screening, process intensification, and process control in the resource and minerals sector.